Numerically Supported Experimental Determination of the Behavior of the Interlayer Bond in Asphalt Pavement. Issue 1 (January 2015) - Wellner, Frohmut; Hristov, Borislav
A good and durable interlayer bond is of high importance for the service life of asphalt pavements. Accordingly, the interlayer bond has long been the subject of active investigation. This paper describes a new test device for cyclic testing of the interlayer bond in double-layered asphalt laboratory specimens. Experiments were carried out to determine the shear stiffness at five temperatures, five normal stresses, and six loading frequencies. All three parameters had a strong influence on the shear stiffness and, therefore, on the operation of the interlayer bond. At low temperatures, high tack coat stiffness as well as good adhesion and aggregate interlocking was present. In contrast, rapid decrease in bonding stiffness occurred at rising temperatures because of the loss of adhesion. In addition, a total loss of interlayer bond occurred at low loading frequencies when no normal force was applied. Furthermore, it was observed that the tack coat amount applied at the interface had a significant effect on the shear stiffness. A numerical model based on the finite element method was developed to simulate the test. With the aid of sigmoidal regressions built for the lowest and highest test temperatures, it was possible to predict the shear stiffness analytically at any shear force and shear displacement and to compare the stiffness with the experimentally determined one.